2005
DOI: 10.1088/0957-4484/17/1/047
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photocatalytic activity of silane-coated and UV-modified nanoscale zinc oxide

Abstract: A new nanoporous material consisting of nano-ZnO particles bridged by –O–Si–O–Si–O– units has been synthesized and characterized. The two-step synthesis involves a precipitation of zinc oxide from a 1 mol l−1 methanolic zinc acetate solution with methanolic KOH in the presence of alkoxyalkylsilanes as coating agents and a UV irradiation of the obtained material in aqueous suspension with air supply. This procedure leads to a nanoscale ZnO network with a high surface area (130 m2 g−1), a better chemical stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…The antibacterial properties of ZnO in powder or nanoparticle forms have also been studied [18][19][20][21][22] and can be further enhanced by ultraviolet light activation [23]. Nanostructured ZnO has interesting properties towards the photocatalytic decomposition of organic pollutants [24] and dyes [25], while La-doped and silane-coated ZnO nanoparticles have recently shown remarkable photocatalytic action against monocrotophos [26] and tetrachloroethylene [27], respectively. Several studies have compared the effectiveness of the photocatalytic properties of ZnO for the inactivation of several pathogens with that of various metallic oxides and demonstrated that ZnO is highly effective in this context [23,28,29].…”
Section: Homentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial properties of ZnO in powder or nanoparticle forms have also been studied [18][19][20][21][22] and can be further enhanced by ultraviolet light activation [23]. Nanostructured ZnO has interesting properties towards the photocatalytic decomposition of organic pollutants [24] and dyes [25], while La-doped and silane-coated ZnO nanoparticles have recently shown remarkable photocatalytic action against monocrotophos [26] and tetrachloroethylene [27], respectively. Several studies have compared the effectiveness of the photocatalytic properties of ZnO for the inactivation of several pathogens with that of various metallic oxides and demonstrated that ZnO is highly effective in this context [23,28,29].…”
Section: Homentioning
confidence: 99%
“…We have already mentioned that the hole diffusion length in ZnO is in the range 0.5-2 µm, thus it is reasonable to assume that some photogenerated holes will be driven towards the surface and reach the ZnO/biofilm interface. The photo-holes can then directly oxidize the bacterial organic matter [26,27]. Alternatively, they can oxidize water to produce hydroxyl OH…”
Section: Homentioning
confidence: 99%
“…[30] The coating with silane prevented crystal growth and agglomeration of the primary oxides. The subsequent photochemical treatment almost completely destroyed the organic fragments of the silane and led to the formation of X-ray amorphous silica ("SiO 2 ").…”
Section: Resultsmentioning
confidence: 99%
“…(© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007) prepare nanoscale ZnO. [30] By precipitating the oxides in the presence of a silane in alcohol, a highly dispersed mixture of the oxides with a high specific surface area [31] is obtained because the silane prevents the growth and agglomeration of the oxide crystals. [32] Subsequently, the organic substituents of the silane are photochemically oxidized and almost completely removed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation